HARDENING OF CASTING AT CONTINUOUSLY-CYCLIC CASTING BY FROSTING - A. M. Bodjako; P. I. Zimonin; I. A. Melnikov; A. A. Suponev (Литьë и металлургия)
The evaluation of changing of the cast temperature in crystallizer is carried out.